Potensi Sektor Pertanian Dan Pengaruhnya Terhadap Penyerapan Tenaga Kerja di Provinsi Aceh - Safrida Safrida; Noratun Juliaviani; Anwar Deli; Latifa Isma (University of Jember, 2022)
An increase will follow the increase in population in an area in the rate of increase in the labor force. This will develop problems caused by the lack of functioning of various sectors so that the readiness of employment opportunities is not commensurate with the population growth rate. With the agricultural sector, people can get food as their basic need. The potential of the agricultural sector can be seen from the value of exports, the area of ​​agricultural land, and the wages of the agricultural sector. The purpose of this study is